Parkinson's disease-associated GPR37 receptor regulates cocaine-mediated synaptic depression in corticostriatal synapses. (18th January 2017) - Rial, Daniel; Morató, Xavier; Real, Joana I.; Gonçalves, Francisco Q.; Stagljar, Igor; Pereira, Frederico C.; Fernández-Dueñas, Víctor; Cunha, Rodrigo A.; Ciruela, Francisco
Graphical abstract: Highlights: A potential role GPR37 in corticostriatal synaptic transmission is proposed. GPR37 genetic deletion does not modify synaptic transmission and short-term plasticity. GPR37 regulates cocaine-mediated synaptic depression in corticostriatal synapses. Abstract: GPR37 is an orphan G protein-coupled receptor highly expressed in the brain. The precise function of GPR37 is still unknown, but a number of evidences indicate it modulates the dopaminergic system. Here, we aimed to determine the role of GPR37 on the control of cocaine-mediated electrophysiological effects (synaptic transmission and short-term plasticity) in corticostriatal synapses. Accordingly, we evaluated basal synaptic transmission and paired-pulse stimulation (PPS) in wild-type and GPR37KO mice slices. Regardless of the genotype, a low concentration of cocaine (2 μM) did not modify basal synaptic transmission. Conversely, a higher dose of cocaine (30 μM) decreased synaptic transmission in both genotypes, although with different intensities: approximately 30% in slices from wild-type mice and 45% in slices from GPR37-KO mice. On the other hand, no differences in PPS ratio were observed between wild-type and GPR37-KO cocaine-treated mice. Overall, our data suggest that GPR37 is involved in cocaine-induced modification of basal synaptic transmission without modifying cocaine effects in short-term plasticity.